Neformalna pogajanja o priznanju krivde - Testen, Ana (Podjetje in delo, 2015)
Informal plea bargaining is a reflection of practice and a shortcut to better results. As they are not regulated by the law, the procedural rules applicable to formal bargaining, e.g. mandatory defence by an attorney, do not apply. In principle, a judge does not participate in the informal plea bargaining although he or she takes the first step to an alternative way of a dispute resolution, i.e. entering into a guilty plea bargain, by calling on the prosecutor to offer a plea agreement to the defendant if the defendant pleads guilty, and to the defendant to plead guilty or not guilty. Both parties are involved in plea bargaining by the judge: the prosecutor must formulate the charges and proposed sanction, and the defendant must plead guilty or not guilty (and consequently accept or refuse the prosecutor's offer). However, it must be noted that the participation of the parties in plea bargaining is voluntary. It is unclear why, in practice, the concept of "informal plea bargaining" has prevailed; the reason for it could possibly be in the concept of formal procedural act. Plea bargaining would also be a possibility, where the parties exchange information on criminal sanctions, admissibility of evidence, etc., and which could be concluded by the admission of guilt. Informal guilty pleas are not binding and are not excluded if no informal guilty plea bargain is entered into, because they are only given as non-binding information in a procedure taking place outside procedural rules. For as long as judges are committed to achieving the (ideal) norm, there will be shortcuts such as informal plea bargaining or informal guilty pleas and increased sanctions if the defendant does not plead guilty.
Keywords: kazenski postopek; kazniva dejanja; krivda; sodišča; sodna praksa; storilci